2007
DOI: 10.1111/j.1365-2893.2007.00900.x
|View full text |Cite
|
Sign up to set email alerts
|

The course of hepatitis C viraemia in transfusion recipients prior to availability of antiviral therapy

Abstract: Knowing the likely distribution of intervals from hepatitis C infection to first RNA-negativity is important in deciding about therapeutic intervention. Prospectively collected sera and data from the Transfusion-transmitted Viruses Study (1974-1980) provide specific dates of infection and pattern of alanine aminotransferase (ALT) elevations. We examined frequency, timing and correlates of spontaneous resolution for 94 acutely infected transfusion recipients followed for a median of 9.5 months. Later, follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 40 publications
5
48
0
3
Order By: Relevance
“…However, intercalation cases were also observed later in HCV infection and after lengthier periods of HCV RNA undetectability, as has previously been reported [6,12,38,39]. This highlights the importance of viral sequencing for classification of HCV reinfection.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…However, intercalation cases were also observed later in HCV infection and after lengthier periods of HCV RNA undetectability, as has previously been reported [6,12,38,39]. This highlights the importance of viral sequencing for classification of HCV reinfection.…”
Section: Discussionsupporting
confidence: 71%
“…The analysis of time to HCV reclearance versus primary clearance only included participants with reclearance during the study period. While the participants with persistent reinfection were all followed for at least 10 months, indicating that future reclearance would be unlikely, late clearance can occur, so there is a small risk of bias from excluding right-censored data (Supplementary Materials) [39]. This is the first study to investigate predictors of HCV reclearance.…”
Section: Discussionmentioning
confidence: 99%
“…Confirmed reinfections represent the gold standard, whereas analyses that include possible reinfections may be subject to misclassification errors, where some transient fluctuations in viral load may have been classified as possible reinfections. This has been shown to occur after more than six months of sustained viraemia [8,36], but is rare after 10 weeks of undetectability (as occurred for all spontaneous clearances in the Networks 2 study), making misclassification unlikely but still possible in the data used here. With respect to the reinfection duration estimates, the slightly longer durations estimated when including possible reinfections as well as confirmed reinfections may be due to such misclassification errors.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies showed that spontaneous clearance usually occurs within the first 6 months of the infection. It has been reported that factors influencing spontaneous clearance positively were being under 30 years of age, female gender, symptomatic infection, IL 28BCC genotype and HCV genotype 1, while independent predictive factors have been determined to be female gender, IL 28 B CC genotype and HCV genotype 1 (10,11,12). Spontaneous clearance was reported in 46-67% of symptomatic cases, while no spontaneous clearance observed in asymptomatic patients (13,14).…”
Section: Observation For Spontaneous Clearancementioning
confidence: 99%